EFFICACY OF SYSTEMIC FUNGICIDES ON THE INCIDENCE OF , SEED GERMINATION AND SEEDLING VIGOUR INDEX OF BLACK GRAM FUSARIUM OXYSPORUM (Journal of Plant Disease Sciences, 2024)
Black gram is a most important summer pulse, which has a great market demand with a good potentiality for trade and export. The production of black gram has ceased at higher rate by many fungi, as fungi infest in seeds. In this research, systemic fungicides were applied on seeds of black gram of artificially infected seeds and naturally infected seeds with mycoflora. Seeds of black gram from two different storage sources were tested for seed-borne fungi. Paper towel method, Standard blotter paper method and Agar plate method were used to isolate seed-borne fungi, in which Standard blotter paper method was found to be the best. Seeds from traditional storage were found to be more infested with seed-borne fungi in comparison to seeds from the market. Among isolated fungi species, four dominant species such as Aspergillus flavus Aspergillus niger Alternaria alternata Fusarium spp  and . Among them was taken for treatment.
Keywords: Black gram; Mycoflora; Fungicides; Fusarium; axysporum